Uma abordagem sobre os elementos contemporâneos da cultura boliviana e suas influências nas empresas estrangeiras - Baptista, Renato Dias (Diálogos Latinoamericanos, 2015)
The culture of a country contains essential elements for the development of production internationalization strategies. This article aims to analyze characteristics of the Bolivian culture and their interfaces in two Brazilian transnational companies with production facilities in Bolivia. For the achievement of the objective, interviews were conducted with executives of Petrobras and Votorantim. Were also interviewed the Consul General in Bolivia Brazil, Colbert Soares Junior and former President of Bolivia, Carlos Mesa Gisbert. The information obtained allowed to emphasize the influence of local culture in the internationalization process.